History of abuse and neglect and their associations with mental health in rescued child labourers in Nepal. (December 2019) - Dhakal, Sandesh; Niraula, Shanta; Sharma, Narayan Prasad; Sthapit, Sabitri; Bennett, Eleanor; Vaswani, Ayesha; Pandey, Rakesh; Kumari, Veena; Lau, Jennifer YF
Objectives: Little is known about rates of childhood maltreatment in low-income countries, particularly among marginalised sectors of society. Economic hardships mean that in such countries, many children and young people are exploited in the labour force and/or are trafficked, placing them at greater risk for being exposed to other forms of maltreatment. Cultural norms endorsing the use of physical and emotional acts to discipline children further exacerbate this risk. Here, we assessed the rates of childhood victimisation experiences and associated mental health problems in Nepalese youth rescued from illegal child labour including trafficking. Methods: One hundred and three young people aged 12–18 years living in out-of-home care institutions and rescued from child labour/trafficking completed translated versions of selected modules from the Juvenile Victimisation Questionnaire, the Youth Inventory and the Strength and Difficulties Questionnaire. Care-home employees responsible for looking after the young people completed the Adolescent Symptom Inventory and the Strength and Difficulties Questionnaire. Analysis described maltreatment frequencies and compared individuals who had and had not experienced any form of maltreatment on the presence/absence of psychiatric diagnoses. Results: Seventy-two percent of participants experienced some form of maltreatment in their lifetime. Rates for each maltreatment type were 46.6% for physical abuse, 40.77% for emotional abuse, 27.2% for sexual abuse and 33% for neglect. Symptoms indicative of anxiety disorders and trauma were commonly reported especially in victims of childhood maltreatment. Conclusions: Our estimates of physical abuse in this at-risk juvenile sample were commensurate to those reported in general-population youth samples in Nepal, but sexual and emotional abuse rates were somewhat lower. The potential presence of anxiety and trauma in this sample that may result from maltreatment requires replication, but underscores an urgent need for routine mental health screening in rescued child labourers during rehabilitation efforts.